Hydrogel supplemented with human platelet lysate enhances multi-lineage differentiation of mesenchymal stem cells - Tong Lei; Yanyan Liu; Shiwen Deng; Zhuangzhuang Xiao; Yanjie Yang; Xiaoshuang Zhang; Wangyu Bi; Hongwu Du (Journal of Nanobiotechnology, 2022)
Abstract Stem cells from human exfoliated deciduous teeth (SHED) can be used as a potential clinical material. But the use of xenogeneic ingredients will increase the risk of zoonotic disease transmission. Human platelet lysate (HPL) is a potential surrogate and used in human cell expansion with reliability in clinical applications. In this study, we synthesized chitosan/gelatin/gellan gum hydrogel supplemented with HPL and investigated the effect of 3D culture for SHED. TMT-tagged proteomics was used to decipher the secretome protein profiles of SHEDs and a total of 3209 proteins were identified, of which 23 were up-regulated and 192 were down-regulated. The results showed that hydrogel supplemented with HPL promoted SHED proliferation. After induction, the hydrogel coating contributed to osteogenic differentiation, adipogenic differentiation and differentiation into neural-like cells of SHED. SHED encapsulated in a hydrogel promotes migration and angiogenesis of HUVEC. In conclusion, our research found that hydrogel supplemented with HPL can be used as a method for SHED in standardized production and can contribute to the clinical application of SHED in cell therapy.